The Analyses of Chemical Components From Oldenlandia hedyotidea (DC.) Hand.-Mazz and Anticancer Effects in vitro - Zhao, Chuanyi; Wei, Mengyuan; Zheng, Yilin; Tao, Weili; Lv, Qian; Wang, Qiongjin; Wang, Shuyun; Chen, Yicun (Frontiers in Pharmacology, 2021)
Hedyotis hedyotidea (H. hedyotidea) also known as sweet tea is a valuable functional food with medicinal potential which has been used for the treatment of cold, cough, gastro-enteritis, heatstroke, Herpes zoster, rheumatoid arthritis, etc. Phytochemicals present in plant foods are in responsible for these diseases to some degree. Nevertheless, detailed information on these chemical components from sweet tea is still scarce. Therefore, we aimed at investigating the phytochemical components of sweet tea using ultra-performance liquid chromatography mass spectrometry (UPLC-MS) and ultraperformance liquid chromatography-triple-time of flight mass spectrometer (UPLC-Triple-TOF-MS), then a main ingredient asperulosidic acid was quantified by ultra-performance liquid chromatography (UPLC). The anticancer activity of the sweet tea extract was assessed using cell proliferation assay and scratch assay on the line of esophageal cancer cell. A total of 10 compounds were identified. These compounds included 5 iridoids, 2 anthraquinones, and 1 Alkaloid. The content of asperulosidic acid in extract of sweet tea dissolved by water was around 42μg·mL -1 and the extract of H. hedyotidea had obvious anticancer effect in vitro. The results are available for the quality control and assessment of H. hedyotidea and it is a promising source of functional ingredients which has potential use in the food and drug industries.